Upstate Abundance, a Variety with Small Round White Tubers and Resistance to Lineage US-23 of Late Blight and Pathotypes Ro1 and Ro2 of the Golden Cyst Nematode - Walter S. De Jong; Xiaohong Wang; Donald E. Halseth; Robert L. Plaisted; Keith L. Perry; Xinshun Qu; Barbara J. Christ; Ken M. Paddock; Matthew Falise (American Journal of Potato Research, 2026)
Upstate Abundance is a fresh market white-fleshed potato cultivar with resistance to both pathotypes Ro1 and Ro2 of the golden cyst nematode ( Globodera rostochiensis ) as well as to late blight ( Phytophthora infestans ) lineage US-23. It was selected from a cross made at Cornell University in 2000 between the Cornell breeding clone NY121 and the fresh-market cultivar Jacqueline Lee and released by the New York Agricultural Experiment Station in 2017. The tubers are small and round with modestly-recessed eyes and smooth skin; total yield across 20 trials in New York and Pennsylvania averaged 36.6 Mg ha − 1 , with about half the yield in tubers less than 4.75 cm in diameter and most of the rest in tubers between 4.75 and 6.4 cm in diameter.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

The evolution of between-sex bonds in primates - Elisabeth H.M. Sterck; Catherine Crockford; Julia Fischer; Jorg J.M. Massen; Barbara Tiddi; Susan Perry; Cédric Sueur; Oliver Schülke; Julia Ostner (Evolution and Human Behavior, 2024)

Brodie, a Dual-Purpose Chipping and Tablestock Variety with Resistance to Pathotypes Ro1 and Ro2 of the Golden Cyst Nematode and Partial Resistance to Pathotype Pa2/3 of the Pale Cyst Nematode - Walter S. De Jong; Xiaohong Wang; Donald E. Halseth; Robert L. Plaisted; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Louise-Marie Dandurand; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2024)

Lehigh, a Variety with Yellow Flesh and Resistance to the Golden Cyst Nematode and Common Scab - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2023)

Memantine treatment does not affect compulsive behavior or frontostriatal connectivity in an adolescent rat model for quinpirole-induced compulsive checking behavior - Milou Straathof; Erwin L. A. Blezer; Christel E. Smeele; Caroline van Heijningen; Annette van der Toorn; Jan K. Buitelaar; Jeffrey C. Glennon; Willem M. Otte; Rick M. Dijkhuizen; Jan Buitelaar; Saskia de Ruiter; Jilly Naaijen; et al. (Psychopharmacology, 2022)
Rationale Compulsivity often develops during childhood and is associated with elevated glutamate levels within the frontostriatal system. This suggests that anti-glutamatergic drugs, like memantine, may be an effective treatment. Objective Our goal was to characterize the acute and chronic effect of memantine treatment on compulsive behavior and frontostriatal network structure and function in an adolescent rat model of compulsivity. Methods Juvenile Sprague–Dawley rats received repeated quinpirole, resulting in compulsive checking behavior ( n = 32; compulsive) or saline injections ( n = 32; control). Eight compulsive and control rats received chronic memantine treatment, and eight compulsive and control rats received saline treatment for seven consecutive days between the 10th and 12th quinpirole/saline injection. Compulsive checking behavior was assessed, and structural and functional brain connectivity was measured with diffusion MRI and resting-state fMRI before and after treatment. The other rats received an acute single memantine (compulsive: n = 12; control: n = 12) or saline injection (compulsive: n = 4; control: n = 4) during pharmacological MRI after the 12th quinpirole/saline injection. An additional group of rats received a single memantine injection after a single quinpirole injection ( n = 8). Results Memantine treatment did not affect compulsive checking nor frontostriatal structural and functional connectivity in the quinpirole-induced adolescent rat model. While memantine activated the frontal cortex in control rats, no significant activation responses were measured after single or repeated quinpirole injections. Conclusions The lack of a memantine treatment effect in quinpirole-induced compulsive adolescent rats may be partly explained by the interaction between glutamatergic and dopaminergic receptors in the brain, which can be evaluated with functional MRI.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Waneta, a Variety with Excellent Chip Color out of Cold Storage, Long Tuber Dormancy, and Resistance to the Golden Cyst Nematode - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Associations of human skeletal muscle fiber type and insulin sensitivity, blood lipids, and vascular hemodynamics in a cohort of premenopausal women - Gordon Fisher; Samuel T. Windham; Perry Griffin; Jonathan L. Warren; Barbara A. Gower; Gary R. Hunter (European Journal of Applied Physiology, 2017)

Lamoka, a Variety with Excellent Chip Color Out of Cold Storage and Resistance to the Golden Cyst Nematode - Walter S. De Jong; Donald E. Halseth; Robert L. Plaisted; Xiaohong Wang; Keith L. Perry; Xinshun Qu; Ken M. Paddock; Matthew Falise; Barbara J. Christ; Gregory A. Porter (American Journal of Potato Research, 2017)

Novel mitochondrial DNA primers for identification of population trends in longnose suckers (Catostomus catostomus) and multispecies identification - Barbara L. Langille; Robert Perry; Donald Keefe; H. Dawn Marshall (Conservation Genetics Resources, 2014)

Marcy: A chipping variety with resistance to common scab and the golden nematode - Walter S. De Jong; Donald E. Halseth; Bill B. Brodie; Keith L. Perry; Joseph B. Sieczka; Barbara J. Christ; Gregory A. Porter; Ken M. Paddock; Michael W. Peck; Robert L. Plaisted (American Journal of Potato Research, 2006)

Differentiation of Gut and Hepatic First-Pass Effect of Drugs: 1. Studies of Verapamil in Ported Dogs - Yong-Hee Lee; Barbara A. Perry; Hee-Sang Lee; Jeevan R. Kunta; John P. Sutyak; Patrick J. Sinko (Pharmaceutical Research, 2001)

Regional Differences in Intestinal Spreading and pH Recovery and the Impact on Salmon Calcitonin Absorption in Dogs - Yong-Hee Lee; Barbara A. Perry; John P. Sutyak; William Stern; Patrick J. Sinko (Pharmaceutical Research, 2000)

Impact of Regional Intestinal pH Modulation on Absorption of Peptide Drugs: Oral Absorption Studies of Salmon Calcitonin in Beagle Dogs - Yong-Hee Lee; Barbara A. Perry; Stacy Labruno; Hee Sang Lee; William Stern; Lisa M. Falzone; Patrick J. Sinko (Pharmaceutical Research, 1999)

Biopharmaceutical Approaches for Developing and Assessing Oral Peptide Delivery Strategies and Systems: In Vitro Permeability and In Vivo Oral Absorption of Salmon Calcitonin - Patrick J. Sinko; Yong-Hee Lee; Vijaya Makhey; Glen D. Leesman; John P. Sutyak; Hongshi Yu; Barbara Perry; Curtis L. Smith; Peidi Hu; Erik J. Wagner; Lisa M. Falzone; Laura T. McWhorter; et al. (Pharmaceutical Research, 1999)